The economic thought of Friedrich List - Hagemann, Harald; Seiter, Stephan; Wendler, Eugen 1937- (Routledge, 2019)
As the world grapples with increased globalization and technological change, Friedrich List's work appears more relevant than ever before. His theory of "productive powers" and his argument for protecting infant industries give us a valuable way of looking at innovation systems, winners and losers in international trade, and the current shift towards economic and political nationalism. Comprising fifteen specially commissioned chapters from a range of international scholars, this book explores many aspects of List's economic thought, including industrial development, political economy, the economics of education, infrastructure and catching-up processes in Asian economies. This volume will be illuminating reading for advanced students and researchers in the history of economic thought, economic history, economic policy and international trade
Description based on online resource; title from digital title page (viewed on December 05, 2018)
Keywords: List, Friedrich / 1789-1846; Economists / Germany; Economics / Germany